Poleward along-shore current pulses on the inner shelf of the Bay of Biscay. (20th September 2016) - Kersalé, M.; Marié, L.; Le Cann, B.; Serpette, A.; Lathuilière, C.; Le Boyer, A.; Rubio, A.; Lazure, P.
Abstract: We analyzed strong events of coastal poleward along-shore currents above 10 cm s −1 and up to more than 50 cm s −1 on the inner shelf (50–80 m depth) of the Bay of Biscay (BoB) from the Spanish coast to the Brittany coast. We used data from four acoustic Doppler current profilers (ADCPs) deployed from July 2009 to August 2011. The goal of this study was to analyze current variability at meso- and subinertial scales and its generation mechanism. These currents occurred all year long and were classified into three types. Events occurring principally in the southern part of the BoB were classified as southern events . Bay-scale events were defined when strong poleward currents were detected over all the shelf, typically stronger on the Spanish and the southern Brittany shelves. Strong events were characterized by depth averaged current velocities over 40 cm s −1 in the southern part of the BoB. At short time lags, the along-shore currents were clearly related to along-shore wind stress at upstream locations. An explanation is provided for longer time lags in terms of coastal trapped wave (CTW) dynamics. The first CTW mode phase speeds were in agreement with the propagation speeds of the fastest events (> 5 m s −1 ), while inner shelf modes could explain the slowest events (∼ 1–3 m s −1 ). The cross-shelf density gradient and the extension of the IPC were also associated with strong coastal poleward along-shore currents. The duration of the events, the vertical structure of the currents and the associated coastal trapped waves were studied in relation with the stratification.